Role of mordenite zeolite in improving nutrient and water use efficiency in Alfisols - V, Girijaveni; K, Sammi Reddy; Ch, Srinivasarao; B M K, Raju; Balakrishnan, Divya; Kundu, Sumanta; Pushpanjali,; Rohit, Jagriti; V K, Singh (Frontiers in Plant Science, 2025)
Poor nutrient use efficiency (NUE) and water use efficiency (WUE) is a predominantly faced problem in semi-arid regions that limit the crop production. This problem can be addressed with the application of zeolite that is a naturally available mineral with very high cation exchange and water holding capacity, which aids in improving NUE and WUE. Moreover, zeolites are safe for the environment and living organisms, and their use in agriculture results in improving physical and chemical properties of soil. Yet, its study is very limited in semi-arid regions of India. Thus, a study was conducted with locally available zeolite at CRIDA, Hyderabad. Zeolite was further characterized using X-ray diffraction (XRD) and SEM, as the type of zeolite collected is unknown from local market. The results of XRD and SEM revealed that the zeolite collected was mordenite zeolite. Our study includes laboratory and pot experiment where laboratory includes sorption and leaching column study to evaluate the zeolite capacity to hold and release the nutrients especially NH4+, P, and K. In this study, the adsorption behaviour of the natural mordenite was examined, and it was found that the maximum adsorption capacity for NH4+, P, and K were estimated as 10.6, 1.08, and 2.15 mg g−1, respectively, suggesting the zeolite has good affinity for N. Furthermore, the column study revealed that there was 15.4% reduction in NH4+–N loss with 10 tonnes zeolite ha−1 + N @ 100 kg ha−1 as compared to N alone, while the reduction was 39.6% with 10 tonnes zeolite ha−1 + N @ 500 kg ha−1 compared to N alone, suggesting that the zeolite could control the release of N as compared to the sole application of N, which was supplied through urea. In addition, pot experiment was carried out with three levels of fertiliser rates, four levels of zeolite, and two levels of moisture in randomised complete block design with three replications to evaluate the changes in soil available nutrients and their uptake in tomato. Results revealed that there was a significant positive impact on yield, water use efficiency, nutrient (N, P, and K) uptake, and soil available nutrients. Highest soil available N, P, and K, crop uptake, and yield were observed due to zeolite application @ 200 kg ha−1 along with 100% recommended dose of fertilization in Alfisols. Thus, zeolite application along with chemical fertilisers can improve the nutrient availability by reducing the leaching losses and improving nutrient use efficiency.